Water desorption characteristic of red gypsum - Lee, Cheng Yee (2015)
Red gypsum (RG) is a waste that generated during the process of titanium dioxide production from ilmenite. It is a soil with reddish colour due to the present of iron. This reddish waste being highly produced every year in Malaysia, which is 341000 tonnes and they are mostly disposed to landfill. In this study, the water desorption characteristic of Red Gypsum are tested as well as physical and chemical properties. The physical and chemical properties of Red Gypsum were determined. Other than that, a suction-water content soil-water characteristic curve (SWCC) is formed. The techniques used with the aim of obtaining the data for drying SWCC are vapour equilibrium and osmotic technique. In osmotic technique, the suction ranged from 0.23 to 3.28 MPa, while in vapour equilibrium technique, suctions used were between 3.6 to 111.77 MPa. . The result of SWCC able to give an important information about Red Gypsum. As a result, Red Gypsum has a soil suction around 22.5 MPa and gravimetric water content around 50 % at air entry value (AEV), while at residual condition, the gravimetric water content is 26% and soil suction is around 38 MPa. In conclusion, RG has the drying suction-water content soil-water characteristic curve which almost the same as yellow bentonite. So, it can have the applications as yellow bentonite.